Catalpol alleviates amyloid- generation and neuronal oxidative stress injury via activating the Keap1-Nrf2/ARE signaling pathway in the immortalized lymphocytes from patients with late-onset Alzheimer’s disease and SKNMC cells co-culture model - Caixia Xiang; Yunwei Lu; Renjuan Hao; Yuyan Wei; Yingchao Hu; Guran Yu (Iranian Journal of Basic Medical Sciences)
Objective(s): To assess the effect of catalpol, the major bioactive constituents of Rehmannia glutinosa, on our Alzheimer’s disease (AD) in vitro model.Materials and Methods: We employed the immortalized lymphocytes (lymphoblastoid cell line, LCL) from late-onset AD patients and co-cultured “them” to mimic the pathological process of late-onset AD and investigated the effect of catalpol on our AD in vitro model.Results: In the co-culture model, AD-derived LCL triggered excessive Aβ1-42 in SKNMC cells due to its high levels of oxidative stress and resulted in neuronal oxidative stress injury through inhibiting Keap1-Nrf2/ARE signaling pathway. Treatment with catalpol and N-acetylcysteine (NAC), an antioxidant, prevented the AD LCL-induced Aβ1-42 overproduction and reduced the level of β-site amyloid precursor protein cleaving enzyme-1 (BACE1) and amyloid precursor protein (APP)-C99. Catalpol and NAC also enhanced the antioxidant capacity and reduced apoptosis in SKNMC cells co-cultured with AD LCL. The anti-oxidative effect of catalpol was antagonized by ML385, the Nrf2 inhibitor. Therefore, we speculate that the antioxidant and anti-apoptotic effects of catalpol are mediated by activating the Keap1-Nrf2/ARE signaling pathway.Conclusion: Catalpol affects the anti-Aβ generation and the antioxidative and antiapoptotic properties in the AD co-cultured model. So, it might be a novel natural drug and offer a potential therapeutic approach for AD.